Semantic gradients in picture-word interference tasks: is the size of interference effects affected by the degree of semantic overlap? - Hutson, James; Damian, Markus F. (Frontiers in Psychology, 2014)
We report two experiments attempting to identify the role of semantic relatedness in picture-word interference studies. Previously published data sets have rendered results which directly contradict each other, with one study suggesting that the stronger the relation between picture and distractor, the more semantic interference is obtained, and another study suggesting the opposite pattern. We replicated the two key experiments with only minor procedural modifications, and found semantic interference effects in both. Critically, these were largely independent of the strength of semantic overlap. Additionally, we attempted to predict individual interference effects per target picture, via various measures of semantic overlap, which also failed to account for the effects. From our results it appears that semantic interference effects in picture-word tasks are similarly present for weakly and strongly overlapping combinations. Implications are discussed in the light of the recent debate on the role of competition in lexical selection.